Profile of Non-Hemorrhagic Stroke Patients Who Received Endovascular Stenting Services at Dr. Kariadi General Hospital Semarang - Freddy Hasudungan Aritonang; Aditya Kurnianto; Yovita Andhitara (Neurointervention Working Group of Indonesian Neurological Association, 2025)
Highlight: This study describes profiles of patients who received endovascular stenting services A descriptive method study was selected to offer a thorough overview ABSTRACT Introduction: Endovascular stenting (ES) is an alternative therapy to carotid endarterectomy (CEA) and best management therapy (BMT) for intracranial and extracranial arterial stenosis with or without symptoms. Atherosclerosis can cause non-hemorrhagic stroke, and the risk factors include diabetes mellitus, dyslipidemia, smoking, hypertension, and advanced age. Objective: This study aimed to determine the profile of non-hemorrhagic stroke patients who received ES services at Dr. Kariadi General Hospital, Semarang. Method: This research used a descriptive method with sampling carried out sequentially using electronic patient medical record data from January 2023 to November 2024. Result: ES services were obtained for 67 patients, of whom 39 were men (58.2%). The largest age groups were between > 50-60 years and > 60-70 years, accounting for 37.3%. The stenosis in the proximal vertebral artery was performed by ES in 70.1% patients. ES was performed on 62.7% patients, with an average stenosis degree of 59.8% in the 50%–69% range (moderate to severe stenosis group). Risk factors for atherosclerosis in this study included hypertension in 67.2% patients and dyslipidemia in 52.2%. There were 71.6% of patients who did not have risk factors for diabetes mellitus. In this study, only 2 patients’ data from medical records were examined for smoking risk factors. Conclusion: Non-hemorrhagic stroke patients who received endovascular stenting services at Dr. Kariadi General Hospital, Semarang, were men in their 50s and 60s, with lesions in the proximal vertebral artery with an average stenosis degree of 59.8%. Risk factors included hypertension, age, and dyslipidemia.